The EFL Students’ Perception of Blended Learning Towards Students’ Motivation in English Subject at Junior High School - Ernawati Sihombing; Erika Sinambela; Sahlan Tampubolon (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aimed to determine the perceptions and motivations of EFL students at SMP St. Ignatius Medan who apply blended learning in English subjects. The collected data were analyzed descriptively and qualitatively. The research findings show that EFL students have a positive perception of the use of blended learning in learning English and an increase in their learning motivation after using this method. This is because 72.9% of students are more comfortable using technology in the classroom, and 53.1% of students have a more interactive and interesting learning experience, even though student feedback is considered to be of lower quality; namely, from the data obtained, only 24% of students easily get feedback from teachers. The main problem for students is that 57.3% of them feel there is a lack of social interaction with classmates and teachers, and 71.9% have problems with poor internet connectivity, which causes them to not fully understand learning material. Student motivation in blended learning is influenced by two factors: the first is the intrinsic factor, where it was found that 57.3% of students felt learning English with blended learning was more interesting and fun. Student motivation related to the extrinsic factor; researchers found that 67.7% of students felt motivated to learn English with blended learning because they could access learning materials more flexibly. From these data, it was found that the impact of learning English using blended learning was due to the intrinsic factor: 94.8% of students felt that English was important for their future, and 84.4% of students felt that learning English was a necessity. from the extrinsic impact factor of blended learning with students' motivation to learn English, 86.4% of students feel that they will get a better job in the future. The research findings show that the use of blended learning can be applied more broadly and effectively in increasing the learning motivation and English skills of EFL students.Â